An Analysis of Intracranial Aneurysms Presenting with Subarachnoid Haemorrhage in Manipal Teaching Hospital Pokhara - Karmacharya, Balgopal; Yogi, Nikunja (Nepalese Journal of Radiology, 2018)
Introduction: Rupture of intracranial aneurysms is the most common cause for spontaneous subarachnoid hemorrhage. It is a devastating stroke with high morbidity and mortality. This study was done to determine the frequency, location and size of aneurysms in patients presenting with spontaneous subarachnoid hemorrhage. Methods: This prospective cross sectional observational study was conducted in the Neurosurgery Unit of Manipal Teaching Hospital from January 2012 to June 2016. All patients who presented with spontaneous subarachnoid hemorrhage and had a positive angiography of brain were included in the study. Results: There were 39 patients who had positive angiographic results. Male: female ratio was 1:2.25. Mean age was 55.79 years. Nine patients had more than one aneurysms. More than 50% of patients were of age group 50-70 years. Anterior circulation aneurysms were found in 90% of patients. Anterior communicating artery was the commonest location of aneurysms. Most of the aneurysms had neck size less than 4 mm. Conclusion: Anterior communicating artery aneurysm was the commonest location of ruptured aneurysms. 23.07% of patients had multiple aneurysms.